2012
DOI: 10.1109/tasc.2011.2180882
|View full text |Cite
|
Sign up to set email alerts
|

Study and Development of the Superconducting Conductor for the Grenoble Hybrid Magnet

Abstract: To produce a continuous magnetic field of at least 8.5 T in a 1.1 m cold bore diameter, the superconducting outsert of the Grenoble Hybrid magnet is based on the novel development of a Nb-Ti/Cu Rutherford Cable On Conduit Conductor (RCOCC) cooled to 1.8 K by a bath of superfluid helium pressurized at atmospheric pressure. The main results of the conductor studies and development are presented after a brief introduction to the specificity of hybrid magnets, namely the electromagnetic couplings between resistive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The maximum hoop stress for the inner coil turn of 1100 mm diameter is equal to 140 MPa. The new superconducting outsert coil of the Grenoble hybrid magnet is based on an innovative conductor development [4], [5]. A Nb-Ti/Cu Rutherford cable of rectangular cross section is soldered on a Cu-Ag stabilizer to form the so-called Rutherford Cable On Conduit Conductor (RCOCC).…”
Section: Superconducting Outsert Coil and Rcoccmentioning
confidence: 99%
See 1 more Smart Citation
“…The maximum hoop stress for the inner coil turn of 1100 mm diameter is equal to 140 MPa. The new superconducting outsert coil of the Grenoble hybrid magnet is based on an innovative conductor development [4], [5]. A Nb-Ti/Cu Rutherford cable of rectangular cross section is soldered on a Cu-Ag stabilizer to form the so-called Rutherford Cable On Conduit Conductor (RCOCC).…”
Section: Superconducting Outsert Coil and Rcoccmentioning
confidence: 99%
“…Results concerning the studies and the developments of the RCOCC are reported in [5] together with a summary of the technical specification.…”
Section: Superconducting Outsert Coil and Rcoccmentioning
confidence: 99%
“…Several sites are at disposal for applied superconductivity: two 50 mm diameter room temperature bores, one providing 25 T with 10 MW and the other 30 T with 20 MW, and a 160 mm diameter room temperature bore providing 20 T with 20 MW (27 T in a hybrid upgrade available in 2015 [6], [7]). Because of a high demand, access to 10 MW is easier than to 20 MW.…”
Section: Experimental Set-upmentioning
confidence: 99%